Adsorption of nonionic surfactant on silica nanoparticles: structure and resultant interparticle interactions - Sharma, Kamendra P.; Aswal, Vinod K.; Kumaraswamy, Guruswamy (Journal of Physical Chemistry B, 2010)
Addition of nonionic surfactant, C(12)E(9), to an aqueous dispersion of charge stabilized silica nanoparticles renders particle aggregation reversible. In contrast, aggregation of the same silica particles in aqueous solutions is irreversible. We use a combination of small-angle X-ray scattering (SAXS) and contrast matching small-angle neutron scattering (SANS) to investigate interparticle interactions and microstructure in dispersions of silica particles in aqueous nonionic surfactant solutions. We show that the silica particles interact through a screened Coulombic interaction in aqueous dispersions; interestingly, this interparticle interaction is hard-sphere-like in surfactant solutions. In surfactant solutions, we show that the final surfactant-particle structure can be modeled as 14 micelles adsorbed (on average) on the surface of each silica particle. This gives rise to the short-range interparticle repulsion that makes particle aggregation reversible, and results in the hard sphere interparticle interaction potential. Finally, we show that adsorption of polyethylene imine on the surface of the silica particles prevents adsorption of surfactant micelles on the particle surface.

Nanoparticle size controls aggregation in lamellar nonionic surfactant mesophase - Venugopal, Edakkal; Aswal, Vinod K.; Kumaraswamy, Guruswamy (Langmuir, 2013)
We show that the size of silica nanoparticles influences the nature of their aggregation in an aqueous solution of a relatively hydrophobic nonionic surfactant, C12E4. We present results for dispersions of silica nanopartides with sizes varying from 8 to 26 nm, in a 75: 25 C12E4/water system, that forms a lamellar phase, L-alpha, at room temperature. Addition of silica particles does not affect the formation of the L-alpha phase. Nanoparticles smaller than about 11 nm aggregate irreversibly in the C12E4/water system. However, nanoparticles larger than about 15 nm aggregate in the L-alpha phase, but are dispersed at temperatures above the L-alpha order-disorder temperature. Thus, in contrast to the smaller particles, aggregation of silica nanopartides larger than about 15 nm is reversible with temperature. We use small-angle neutron scattering (SANS) demonstrate that these results can be explained by the size-dependent wrapping of nanoparticles by surfactant bilayers. Larger particles, above 15 nm in size, are sterically stabilized by the formation of an adsorbed surfactant bilayer. The cost of bilayer bending inhibits adsorption onto the highly curved surfaces of smaller particles, and these ``bare'' particles aggregate irreversibly.

Effect of self-assembly on triiodide diffusion in water based polymer gel electrolytes: an application in dye solar cell - Soni, S. S.; Fadadu, K. B.; Vekariya, R. L.; Debgupta, Joyashish; Patel, K. D.; Gibaud, A.; Aswal, Vinod K. (Journal of Colloid and Interface Science, 2014)
The preparation of ordered polymer gels from the amphiphilic block copolymers, Pluronic (R) F77, P123 and polyethylene glycol in the presence of ionic liquid, iodine and organic additives is presented. At 35%(w/w) concentration these copolymers (F77 and P123) self-assembled into cubic liquid crystalline phase in aqueous solution and characterized by using SAXS and AFM measurements. The effects of micellar aggregation formed by polymers on the ionic transport and triiodide diffusion have been studied by electro-chemistry and SANS experiments. The ionic migration or triiodide diffusion through these polymer gels is found to be affected by the PEO/PPO content in the polymer backbone. These gels were successfully employed as an electrolyte in a dye sensitized solar cell. A remarkable solar to electricity conversion efficiency and good stability was obtained using Pluronic (R) F77 based gel, which is attributed to its thermoreversible sol to gel transition. (C) 2014 Elsevier Inc. All rights reserved.
Keywords: Amphiphilic block copolymer; Dye solar cell; Micellar nanochannels; SANS; SAXS; Self-assembly; Water based gel electrolytes

Effect of the branching pattern of hydrophobic dendrons on the core structure of linear-dendritic copolymer micelles - Kalva, Nagendra; Aswal, Vinod K.; Ambade, Ashootosh V. (Macromolecular Chemistry and Physics, 2014)
Hydrophobic dendrons based on different branching patterns, viz. 3,5-di- and 3,4,5-trisubstituted phenyl rings, consist of the same backbone but exhibit different sizes, shapes, and hydrophobic densities. These dendrons are attached to poly(ethylene glycol) and the core properties of the copolymer micelles are investigated in tetrahydrofuran (THF)/water mixtures by neutron scattering. Two polymers with intermediate hydrophobicity are studied further with variations in the solvent composition and the temperature. The aggregation numbers for 3,4,5-based dendron copolymers are lower, with more THF molecules of solvation compared with the 3,5-based dendron copolymer, the difference being greater at higher generations due to different molecular shapes. The micellar core size increases in small steps with dendron size so that dye encapsulation is tuned.
Keywords: diblock copolymers; linear-dendritic copolymers; micelles; neutron scattering; structure-property relations

Silk fibroin-sophorolipid gelation: deciphering the underlying mechanism - Dubey, Parul; Kumar, Sugam; Aswal, Vinod K.; Ravindranathan, Sapna; Rajamohanan, Pattuparambil R.; Prabhune, Asmita; Nisal, Anuya (Biomacromolecules, 2016)
Silk fibroin (SF) protein, produced by silkworm Bombyx mori, is a promising biomaterial, while sophorolipid (SL) is an amphiphilic functional biosurfactant synthesized by nonpathogenic yeast Candida bombicola. SL is a mixture of two forms, acidic (ASL) and lactonic (LSL), which when added to SF results in accelerated gelation of silk fibroin. LSL is known to have multiple biological functionalities and hence hydrogels of these green molecules have promising applications in the biomedical sector. In this work, SANS, NMR, and rheology are employed to examine the assembling properties of individual and mixed SLs and their interactions with SF to understand the mechanism that leads to rapid gelation. SANS and NMR studies show that ASL assembles to form charged micelles, while LSL forms micellar assemblies and aggregates of a mass fractal nature. ASL and LSL together form larger mixed micelles, all of which interact differently with SF. It is shown that preferential binding of LSL to SF causes rapid unfolding of the SF chain leading to the formation of intermolecular beta sheets, which trigger fast gelation. Based on the observations, a mechanism for gelation of SF in the presence of different sophorolipids is proposed.

pH dependent sophorolipid assemblies and their influence on gelation of silk fibroin protein - Dubey, Parul; Kumar, Sugam; Ravindranathan, Sapna; Vasudevan, Sahana; Aswal, Vinod K.; Rajamohanan, Pattuparambil R.; Nisal, Anuya; Prabhune, Asmita (Materials Chemistry and Physics, 2018)
Sophorolipid (SL), a bio-derived surfactant is an excellent gelling agent for natural fibrous protein, silk fibroin (SF) leading to potential biomedical applications. Interaction of SF with SL has been shown to accelerate the formation of hydrogel with the rate being dependent on the form of SL used. Here, we examine the effect of pH on SL-SF interaction and gel formation by employing rheology, fluorescence spectroscopy, SANS and NMR. The results indicate that the size of SL assemblies decrease as pH increases from acidic to alkaline and significantly impacts the association of SL and SF. The association of SF and SL is mainly via hydrophobic interactions, with the SL molecules forming bead like structures along the SF chain. The increased charge on the acidic form of SL at higher pH results in greater repulsion between acidic SL molecules, which are bound to the hydrophobic sites of SF, leading to rapid chain unfolding and subsequent gelation. (C) 2017 Elsevier B.V. All rights reserved.
Keywords: Assemblies; Nuclear magnetic resonance spectroscopy; pH; Silk fibroin; Small angle neutron scattering; Sophorolipid

Silk fibroin-sodium dodecyl sulfate gelation: molecular, structural, and rheological insights - Hirlekar, Swarali; Ray, Debes; Aswal, Vinod K.; Prabhune, Asmita; Nisal, Anuya; Ravindranathan, Sapna (Langmuir, 2019)
A gelling agent is necessary to accelerate sol to gel transition in an aqueous solution of silk fibroin (SF), which otherwise takes several days to complete. In this paper, we investigate the mechanism of gelation of Bornbyx mori SF by a model anionic surfactant, sodium dodecyl sulfate (SOS). Even though interactions between SDS and proteins have been extensively investigated, most of these studies have focused on globular proteins, which undergo denaturation. The interaction with a fibrous protein such as SF is different and results in an altered secondary structure leading to gelation. In this work, the concentration-dependent gelation process of the SF-SDS system is examined using rheology, SANS, FTIR, and NMR. We observed preferential binding of SDS to specific regions on the SF chain, which aids structural changes favoring beta-sheet formation. We propose a mechanism for the accelerated sol-gel transition in the SF-SDS system.

Lauric acid sophorolipid: accelerating the gelation of silk fibroin - Hirlekar, Swarali; Ray, Debes; Aswal, Vinod K.; Prabhune, Asmita A.; Nisal, Anuya (ACS Omega, 2020)
Silk fibroin (SF) hydrogels find wide applications in tissue engineering. However, their scope has been limited due to the long gelation time in ambient conditions. This paper shows the reduction in gelation time of silk fibroin to minutes upon doping with a newly synthesized lauric acid sophorolipid (LASL). LASL comprises a fatty acid, lauric acid (with a 12-carbon aliphatic chain), that is derivatized by glucose molecules using a non-pathogenic yeast Candida bombicola. LASL was characterized using spectroscopic (Fourier transform infrared spectroscopy) and chromatographic (high-performance liquid chromatography, thin-layer chromatography, and high-resolution mass spectrometry) methods. This gelation of SF is comparable to the effect of an anionic surfactant, sodium dodecyl sulfate (SDS). The microstructure of SF-LASL hydrogels was investigated by small-angle neutron scattering (SANS) measurements and exhibited the beads-on-a-necklace model. The rheological properties of these hydrogels show similarity to SF-SDS hydrogels, therefore presenting a greener alternative for tissue engineering applications.